Response surface methodology‐optimized co‐fermentation of pigeon pea okara by Rhizopus oligosporus and Yarrowia lipolytica and its application for vegetable paste. Issue 5 (11th April 2022) - Zhang, HaoRan; Chen, Chao‐Jung; Chen, Bang‐Yuan
Abstract: Introduction: Pigeon pea ( Cajanus cajan ) is a perennial legume usually consumed directly or processed into pigeon pea milk. Pigeon pea okara (PPO) contains 15.5 – 28.8% protein, 56% carbohydrate, as well as vitamins, minerals, and dietary fiber, making it a valuable food material or other applications. This study examines co‐fermentation of PPO by Rhizopus oligosporus and Yarrowia lipolytica to maximize its nutritional value. Methods: The response surface methodology (RSM) with Four variables and five levels central composite design was used to optimize the co‐fermentation conditions including fermentation temperature, R. oligosporus and Y. lipolytica inoculum concentrations, and fermentation time. Results: Solid‐state co‐fermentation significantly increased the total phenolic, total flavonoid, and protein contents, with SDS‐PAGE revealing protein molecular weights generally < 10 kDa. The optimal fermentation condition was using 5.05 × 10 5 spores/g R. oligosporus and 5.05 × 10 5 CFU/g Y. lipolytica at 39°C for 48 hrs. Sensory analysis and shelf‐life testing were then performed on vegetable pastes prepared using optimally fermented PPO. Vegetable paste prepared with 35% fermented PPO content had comparable overall acceptability to paste made with 35% unfermented PPO, and a 14‐day shelf‐life at 4°C. Conclusion: In summary, RSM‐optimized, solid‐state co‐fermentation is an effective method to improve the nutritional value of PPO.